2019
DOI: 10.1016/j.yebeh.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of health sciences students regarding epilepsy at the end of their curriculum in Benin

Abstract: Objective:The main objective of this study was to evaluate the knowledge, attitudes and practices (KAP) of health sciences students regarding epilepsy at the end of curriculum in Benin. Methods: We conducted a cross-sectional survey among medical, pharmacy, nursing and midwife students in their last-year of health sciences training in University of Abomey-Calavi in Benin. Students completed a self-administered questionnaire, containing items addressing demographics, epilepsy treatment, diagnosis, clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The social roles played by the students and the frequency of their interactions with PWE may have had a favorable impact on their perceptions. As their knowledge levels rose, students' views toward epilepsy tended to improve similarly to the findings of Vodougnon et al [52]. Numerous research have demonstrated that students' views towards epilepsy improved when their knowledge scores rose [13,47,53].…”
Section: Epilepsy Attitudesupporting
confidence: 72%
“…The social roles played by the students and the frequency of their interactions with PWE may have had a favorable impact on their perceptions. As their knowledge levels rose, students' views toward epilepsy tended to improve similarly to the findings of Vodougnon et al [52]. Numerous research have demonstrated that students' views towards epilepsy improved when their knowledge scores rose [13,47,53].…”
Section: Epilepsy Attitudesupporting
confidence: 72%
“…We chose for every professional category, the institution training the largest number of students: Ecole Nationale de Santé Publique (ENSP—National School of Public Health), which trains the largest number of nurse and midwife students and Université Joseph Ki‐Zerbo (UJKZ), which is the only University training pharmacy students and which trains the largest number of medical students. The questionnaire was based on documents from World Health Organization, , World Health Organization, talking about knowledge, attitude and practice of mental health as well as questionnaires used in Benin (Vodougnon, ).…”
Section: Methodsmentioning
confidence: 99%
“…Paper case report forms (CRF) including standardized self‐administered questionnaires adapted from WHO resources regarding the diagnosis and management of mental diseases (Vodougnon, ; World Health Organization, , , ). The questionnaires were focused on depression and psychoses (essentially schizophrenia and puerperal psychosis) because these two diseases are amongst the most burdensome in mental health.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, there are more GPs trained in Cuba (46.7%) than in Congo (26.3%) (Table 1). The predominance of GPs trained in Cuba is explained The deficit in knowledge among our participants could be also explained by other factors, such as: the lack of internships for some students in the neurology department; the learning environment; learning styles and teaching modes that do not help to reduce uncertainty about what students need to learn; the long duration of medical school, which can lead to a loss of the initial knowledge acquired; stress [60]- [67].…”
Section: Discussionmentioning
confidence: 98%